CONTROL DIFFUSION PROCESSES WITH LIPSCHITZ CONTINUITY OF DRIFTS - Dharmawan, Komang (Jurnal Matematika; Vol 2 No 1 (2012), 2012)
Control diffusion processes has been found in a wide field of applications as in stochastic optimal control and in mathematical finance via the theory of hedging and nonlinear pricing theory for imperfect markets. In this paper we discuss the control diffusion process with time and space dependent coefficients and local Lipschitz continuity of the drift. The results show that the controlled process Xs;;u t is independent of control u for a constant.
Keywords: Stochastic Differential Equations, Lipschitz continuity, Control Diffusion Process